The Impact of Renewable Energy Sources on Global Climate Change - Esra Deniz Güner; Emine Su Turan (Doğal Afetler ve Çevre Dergisi, 2017)
With the industrialization process, humanity has had to face the problem of global climate change through the intensive use of fossil fuels since the 1870s. This problem is seriously affecting all countries of the world regardless of the level of development. Renewable energy or alternative energy sources have been advocated in recent years, which is the most agreed proposition that has become prominent on the conservation of nature. With global warming, climate change, and scarcity of limited natural resources, the forms of energy and production that do not pollute nature have become one of the priority demands of the states especially since the signing of the Kyoto Protocol. In this study, the issue of global climate change and the importance of disseminating the use of renewable energy resources in respect to managing this problem were revealed.